Anatomical Changes During Laparoscopic Procedures - O. V. Galimov; V. O. Khanov; R. R. Saifullin; D. O. Galimov; M. А. Karimov (Креативная хирургия и онкология, 2020)
Determining the exact sizes of anatomical structures play a very important today in laparoscopic surgery. This makes it possible to make a correct selection of gauges of instruments needed, prosthetic materials, and to make decisions regarding the further strategy of the surgical procedure. The device developed at the clinic has proven itself in everyday clinical practices. It is currently used in laparoscopic operations for hiatal hernias, choledoch measurements in patients with choledocholithiasis, stomach stump size measurements during the resection in patients with morbid obesity. The presented clinical case serves to confirm that obtaining objective data in video endoscopic surgery makes it possible to choose the optimal treatment strategy.